Educação sexual para adolescentes e jovens : o que prevêem os documentos públicos nos níveis Federal e Estadual em São Paulo - Sfair, Sara Caram (2012)
The concept of adolescence and youth are social-historical-cultural constructions and delimit distinct audience, with their own demands. Therefore, their specificity must be considered to the elaboration of official proposals. Regarding sexuality and sex, the conception developed through history, the moral and values influence the sexual education currently proposed. In this Dissertation we discussed the relevance to the promotion of autonomy or, in the contrary sense, to the maintenance of repressing values. From the theoretical framework, we suggest to analyze the official proposals related to sexual education for adolescents and young provided by federal and by São Paulo state documents. For this, we used the documental analyses of published works in federal and São Paulo state, between 1990 and 2010. This a relevant period because it represents 20 years of Child and Adolescent Statute, promulgated in 1988 and a mark of legal reference for this population. The total number of documents was 106, and after selected them, rested 25. 76% of these documents did not use sexual education or sexual orientation terms, but used mainly prevention term. The sexual orientation term had the meaning of sexual diversity for 60% of the cases. Only for four cases there was the differentiation of adolescence and youth and all 25 documents used 12 different age groups. The Ministry of Health is the Ministry with the higher number of proposals, with 14 or 56%, but proposes to intersectionality in education in 11, showing the school institutions recognition as a suitable place to achieve the adolescent and youth population. 80% of the documents were related to different professionals of different areas, reporting them the guidelines to the project realization. We concluded there was a predominance of proposals arising from health departments. We also concluded there was a predominance of proposals of health area, even the school is cited as privileged site for the actions. Even the documents advanced in their prepositions, others documents noticed ways to the repressive actions, including the fear of sexuality practice in adolescences and young people. The education needs to appropriate of the discussion about this theme, maximizing the health area proposals and the conception of sexuality and sex exercise as human right.